The Semantics of the Preposition khɔ̌ɔŋ in Thai - แอบเงิน, สรณ์; เทพกาญจนา, กิ่งกาญจน์ (Journal of Letters, 2018)
It is known among Thai language users that the preposition khɔ̌ɔŋ in Thai is used to express possessive relations between two entities. The concept that readily comes to mind when the language users think about “possession” is ownership. However, there are other types of relations subsumed under linguistic possession expressed by the preposition khɔ̌ɔŋ. The purpose of this paper is, therefore, to identify the possible semantic relations between possessed nouns and possessor noun phrases in nominal constructions with the preposition khɔ̌ɔŋ in Thai. The 2,700 data were collected from the Thai National Corpus. It was found that the semantic relations expressed by the possessive marker khɔ̌ɔŋ could be divided into at least 7 types: 1) ownership, 2) body part relationships, 3) interpersonal relationships, 4) part-whole relations, 5) attributes-attribute holders, 6) predication-participant relations, and 7) whole-content relations.